KEPUTUSAN RUMAHTANGGA PETANI PADI MELAKUKAN ALIH FUNGSI LAHAN KE PERIKANAN DI KABUPATEN MUSI RAWAS - Fifian; Mulyana, Andy; Asmani, Najib; Yunita (AGRIPITA JOURNAL, 2017)
The Decision of Farmer Households Doing Land Transfer Function To Fishery at Musi Rawas Regency. This study aimed to analyze the factors that influence the farmer households in the conversion of wetland into fisheries. Research has been conducted in the month of January to May 2015. The research location is determined by deliberate on the five villages in the district of Musi Rawas Regency (Sukamana, Sri Kemuning, Paduraksa, Air Deras, and Sukarame Village) with the consideration of the sample rice farmers who have done land conversion to the fishery, where there as many as 34 farmers who did land conversion to fisheries. The method used in this study is the survay method and sampling method used was multistage stratified random sampling, by counting areas or locations that the majority of farmers have switched from paddy farming. Data processed by logit analysis. Based on the analysis results obtained factors that influence the decision to switch to farmer households fishery is the income from fishery, number of family and the price of paddy at the farmer’s level.